Editorial - Gimbut, Magdalena (Polskie Studia Krajobrazowe, 2020)
To paraphrase the old Greek proverb, we may say, that the landscape is in the eye, or mind, of the beholder. It is the sum of people’s experiences existing somewhere on the border between people and the environment they live in. The landscape is apprehended and judged by people who experience it aesthetically, according to its utilitarian purposes, the comfort or the labor and trouble it brings. Quite often it is evaluated according to values which people believe are important, cultural factors, imagination, or associations with childhood. When people talk about places, they say more about their fears, loves, and worldviews. This way, the landscape becomes a kind of story people live in. This story is crucially important for people’s identity; it co-creates it; it emphasizes their social position and reflects the picture of themselves they keep in their minds. The landscape says more about those who narrate it than the narration says about the people and places which are included in it. The landscape is a phenomenon which is reconstructed through a medium. This medium can take the shape of memory, tourist tracks, museums, photography, movies, etc. All of them, one way or another, using their specific narration, create reality. Wittingly or unwittingly, those narrations take their inspirations from politics, religion, ideology, or simply entertainment. This is why we may also say that the landscape is invented through narration.